2021
DOI: 10.1177/1369433221997716
|View full text |Cite
|
Sign up to set email alerts
|

Review on impact response of reinforced concrete beams: Contemporary understanding and unsolved problems

Abstract: Designing protective reinforced concrete (RC) beams against impact loadings is a challenging task. It requires a comprehensive understanding of the structural response of RC beams subjected to impact loads. Significant research efforts have been spent to unveil the impact response of RC beams by using analytical models, experimental testing, or numerical investigations. However, these studies used various assumptions in the analytical derivations and different test setups in the impact testing, which led to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 110 publications
(253 reference statements)
1
3
0
1
Order By: Relevance
“…During impact loading, it is therefore possible to initiate global shear failure (static flexural shear failure) and local shear failure (shear plug) for statically flexure-critical RC beams. The same conclusions are reported in the review of the impact response of RC beams, presented in [5]. The local shear failure was explained as an effect of only part of the beam resisting the impact force by its inertia in the early stages of the response, where the stress wave propagation has a significant influence.…”
Section: Introductionsupporting
confidence: 67%
“…During impact loading, it is therefore possible to initiate global shear failure (static flexural shear failure) and local shear failure (shear plug) for statically flexure-critical RC beams. The same conclusions are reported in the review of the impact response of RC beams, presented in [5]. The local shear failure was explained as an effect of only part of the beam resisting the impact force by its inertia in the early stages of the response, where the stress wave propagation has a significant influence.…”
Section: Introductionsupporting
confidence: 67%
“…This observation is in accordance with the findings observed by other researchers (Cotsovos, 2010; Pham and Hao, 2017a; Zhao et al, 2017). Some suggested that the negative reaction force was caused by the stress wave propagation (Cotsovos, 2010; Pham and Hao, 2017a; Pham et al, 2021; Saatci and Vecchio, 2009). However, the up-to-date investigation has proven that the negative reaction force is more likely to be induced by the high modal responses (Hao et al, 2021), which is determined by the natural frequencies (geometric and physical parameters) and the impact energy.
Figure 14.Illustration of time histories of impact and reaction forces.
…”
Section: Results and Analysismentioning
confidence: 99%
“…The connection configurations had a limited effect on the peak impact force under the first impact because of the same impact energy and contact stiffness at the impact zone as summarized in Ref. [46]. However, in the subsequent impacts, the peak impact force acting on the specimens were different because the joints with different connection configurations experienced different residual deflections of beam and damage after each impact.…”
Section: Discussion Of the Impact Performance Of Different Wet Connec...mentioning
confidence: 99%